Polymorphisms of Insulin-Like Growth Factor 1 Pathway Genes and Breast Cancer Risk - Shi, Joy; Aronson, Kristan J.; Grundy, Anne; Kobayashi, Lindsay C.; Burstyn, Igor; Schuetz, Johanna M.; Lohrisch, Caroline A.; SenGupta, Sandip K.; Lai, Agnes S.; Brooks-Wilson, Angela; Spinelli, John J.; Richardson, Harriet (Frontiers in Oncology, 2016)
Genetic variants of insulin-like growth factor 1 (IGF1) pathway genes have been shown to be associated with breast density and IGF1 levels, and therefore may also influence breast cancer risk via pro-survival signalling cascades. The aim of this study was to investigate associations between IGF1 pathway single nucleotide polymorphisms (SNPs) and breast cancer risk among European and East Asian women, and potential interactions with menopausal status and breast tumor subtype. Stratified analyses of 1,037 cases and 1,050 controls from a population-based case-control study were conducted to assess associations with breast cancer for 22 SNPs across five IGF-1 pathway genes in European and East Asian women. Odds ratios were calculated using logistic regression in additive genetic models. Polytomous logistic regression was used to assess heterogeneity by breast tumor subtype. Two SNPs of the IGF1 gene (rs1019731, rs12821878) were associated with breast cancer risk among European women. Four highly linked IGF1 SNPs (rs2288378, rs17727841, rs7136446, rs7956547) were modified by menopausal status among East Asian women only and associated with postmenopausal breast cancers. The association between rs2288378 and breast cancer risk was also modified by breast tumor subtype among East Asian women. Several IGF1 polymorphisms were found to be associated with breast cancer risk and some of these association were modified by menopausal status or breast tumor subtype. Such interactions should be considered when assessing the role of these variants in breast cancer etiology.